Improving the performance of an AUV hovering system by introducing low-cost flow rate control into water hydraulic variable ballast system. (1st October 2016) - Zhao, Xufeng; Liu, Yinshui; Han, Mingxing; Wu, Defa; Li, Donglin
Abstract: Water hydraulic variable ballast system (WHVBS) is a competitive mechanism to realize the hovering system which is one of the most popular ways to expand the maneuvering capability of AUVs. However, the WHVBSs equipped in AUVs almost were on–off type without controlling the flow rate of the in/out ballast water, which limits the hovering performance of the AUVs operated in complex underwater environment. In this paper, three novel types of WHVBS, which supports one or two low cost means to control the flow rate of ballast water, have been proposed to improve the performance of an AUV hovering system. A torpedo-like AUV equipped with WHVBS was used as a simulation platform to verify the effectiveness of the proposed WHVBSs. Numerical simulation results support the idea that compared with the commonly used on–off type WHVBS, the WHVBSs introduced flow rate control can significantly improve the hovering performance of the AUV, especially in the situations with unfavorable sea wave disturbances. Additionally, the statistics on water usage of different WHVBSs in numerical simulation indicated that the novel WHVBSs have the potential to extend the mission duration of AUV. Highlights: Three novel types of WHVBS have been proposed and detailed illustrated in this paper. The proposed WHVBSs can be refitted from commonly used on-off type WHVBS at low cost. Using flow rate control can significantly improve the hovering performance of an AUV. The novel WHVBSs have the potential to extend the mission duration of AUV.